SAT0519 Interstitial lung disease in anca-associated vasculitis patients:comparison with idiopatic pulmonary fibrosis and interstitial pneumonia with autoimmune features. (12th June 2018) - Abril, A.; Kwon, M.; Rojas, C.; Khoor, A.; Mira-Avendano, I.
Abstract : Background: Patients with ANCA-positive vasculitis may develop interstitial lung disease (ILD), it is an uncommon but increasingly recognised manifestation. Clinical characteristics and prognosis are not well known in these patients. The largest report to date is from East Asia describing microscopic polyangitis (MPA) as the most common association with ILD. Objectives: To describe the cliniccal manifestatiions and response to therapy of patients with AAV and ILd compared with patients with idiopathic pulmonary fibrosis (IPF) and interstitial pneumonia with autoimmune features (IPAF) Methods: We conducted a retrospective 10 year chart review at the Mayo Clinic Florida, including patients with confirmed diagnoses of both AAV and ILD done by expert rheumatology and pulmonology clinical evaluations. Clinical characteristics of ANCA-ILD in 24 patients were compared to 29 patients with idiopathic pulmonary fibrosis (IPF) and 22 patients with interstitial pneumonia with autoimmune features (IPAF), which were confirmed by applying the IPF diagnostic criteria based on the most recent ATS guidelines and IPAF criteria defined by Fischer and colleagues, respectively. Results: We identified 24 ANCA-ILD patients. 14 patients had MPA, 12 patients had granulomatosis with polyangitis (GPA), and 2 patients had eosinophilic granulomatosis with polyangitis (EGPA). 54% were female and mean age was 70. In half of the ANCA-ILD patients, vasculitis presented prior to ILD, mainly MPA, 36% of patients presented with ILD first, most of them with GPA. The rest presented with ILD and vasculitis at the same time. Usual interstitial pneumonia (UIP) was the most common radiographic pattern. Honeycombing was more common in MPA compared to GPA patients. Ground glass opacity was present in 5 (63%) of GPA and in 5 (36%) of MPA patients. Most MPA patients had positive anti-MPO antibody and p-ANCA. Only one GPA patient had positive anti-MPO antibody and two were p-ANCA positive. The majority of the GPA patients were positive for anti-proteinase-3 antibody and c-ANCA. The mainstay of treatment was corticosteroids. Rituximab was used in 14 patients. The decline in functional vital capacity (FVC) and diffusing capacity (DLCO) was most marked in IPF group, followed by ANCA-ILD and then the IPAF group (Δ FVC, −0.5, –0.5, and 0.3 L/s; Δ DLCO, −3.7, –3.6, and −0.1, respectively). In a similar manner, survival was poorest in IPF, followed by ANCA-ILD and was best in the IPAF group. Conclusions: This is, to our knowledge, the largest case series of clinically confirmed AAV with ILD in North America. Sizable number of GPA with c-ANCA positive patients presenting concomitant ILD is a novel observation for the clinical characteristics of ANCA-ILD that contradicts previous epidemiology of ANCA-ILD. Our data is also of value by adding prognostic information in an era of newer therapeutics, such as rituximab. In addition, the intermediate prognosis of ANCA-ILD, between IPF and IPAF, is very interesting especially after the new classification IPAF. Disclosure of Interest: None declared